THE EFFECT OF JIGSAW TYPE OF COOPERATIVE MODEL ON THE LEARNING OUTCOMES OF STUDENTS SOCIAL SCIENCE IN ELEMENTARY SCHOOL - Ully Fauziah; Taufina Taufina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research aims to determine the effect of Jigsaw Cooperative learning on student learning outcomes in social studies learning in grade 5 of elementary school. This research was motivated by the fact that teachers tended to apply conventional learning models, learning was often dominated by teachers, so the learning process was less attractive to students, and student learning outcomes in social studies learning still tended to be low. This research was a quantitative research with quasy experimental research design. The sampling was taken by using purposive sample technique. The research sample consisted of 50 people with a population of 50 people. The treatment that researchers gave to the experimental class aimed to determine the effect that occurred on learning outcomes using the Jigsaw Cooperative Learning Method. The instrument used in collecting data in the form of objective tests with multiple choice forms. Based on the research that has been done, the obtained t-count> t-table was 4.5378> 2.011 with α = 0.05 which meant that H0 was rejected. The average student learning outcomes measured by posttest after learning, namely in the 86.88 experimental class and 75.63 control class. So Ha accepted that there was an influence of the use of Jigsaw Cooperative learning model on student learning outcomes in social studies learning in grade 5 of elementary school.